2017
DOI: 10.1007/s11655-017-2964-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astragalus Polysaccharide on Mechanical Characterization of Liver Sinusoidal Endothelial Cells by Atomic Force Microscopy at Nanoscale

Abstract: The values of Young's modulus increased along with increasing concentrations of APS, suggesting that the stiffness of SECs increases gradually as a function of APS concentration. The observed changes in SEC mechanical properties may provide a new avenue for mechanistic research of anti-hepatic fibrosis treatments in Chinese medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…When studying the effects of Astragalus polysaccharide (APS), which is the primary effective component of the Chinese herbal medicine Astragalus membranaceus , on nanoscale mechanical properties of LSECs in rats, we found that as APS concentration increased, the value of Young’s modulus presented an increasing trend, and the surface topography demonstrated that APS was capable of increasing the total area of fenestrae. The observed changes in mechanical properties of LSECs may provide a new therapeutic strategy for mechanistic research of anti-hepatic fibrosis treatments in Chinese medicine[ 52 ].…”
Section: Lsecs In Liver Fibrosismentioning
confidence: 99%
“…When studying the effects of Astragalus polysaccharide (APS), which is the primary effective component of the Chinese herbal medicine Astragalus membranaceus , on nanoscale mechanical properties of LSECs in rats, we found that as APS concentration increased, the value of Young’s modulus presented an increasing trend, and the surface topography demonstrated that APS was capable of increasing the total area of fenestrae. The observed changes in mechanical properties of LSECs may provide a new therapeutic strategy for mechanistic research of anti-hepatic fibrosis treatments in Chinese medicine[ 52 ].…”
Section: Lsecs In Liver Fibrosismentioning
confidence: 99%
“…In addition, bile stasis causes cholestatic liver fibrosis ( Hasegawa et al, 2021 ), intraperitoneal administration of Astragaloside in a bile duct ligation model of hepatic fibrosis in rats attenuated the development of fibrosis as assessed by collagen deposition, myofibroblast activation, and hepatobiliary function ( Yongping et al, 2015 ). Furthermore, fibrosis leads to changes in cellular structure and mechanical properties ( Natarajan et al, 2017 ), Astragalus polysaccharide can increase the stiffness of liver sinusoidal endothelial cells, which may provide a new mechanism for Chinese medicine to fight hepatic fibrosis ( Lu et al, 2018 ). Calycosin can reduce α-SMA in both carbon tetrachloride-induced hepatic fibrosis mice and non-alcoholic steatohepatitis mice, collagen I decrease is also observed in the carbon tetrachloride model, this is related to multiple mechanisms, including inhibiting oxidative stress, matrix metalloproteinase-1/tissue inhibitor of metalloproteinase-1 (MMP-1/TIMP-1) system and activating janus kinase 2- signal transducer and activator of transcription 3 (JAK2-STAT3) pathway, while Calycosin activates farnesoid X receptor (FXR) to attenuate hepatic fibrosis in non-alcoholic steatohepatitis mice ( Duan et al, 2017 ; Zhang et al, 2021a ).…”
Section: Effect Of Astragalus On Fibrotic Diseasesmentioning
confidence: 99%